Patient Counseling and Preferences for Elective Repeat Cesarean Delivery - Susan Folsom; M. Sean Esplin; Sean Edmunds; Torri D. Metz; G. Marc Jackson; T. Flint Porter; Michael W. Varner (Thieme Medical Publishers, Inc., 2016)
Abstract Objective We sought to identify factors influencing a woman's decision to have an elective repeat cesarean delivery (ERCD) versus vaginal birth after cesarean (VBAC). Methods and Materials A prospective study at two academic medical centers of women with one prior cesarean, and no contraindication to a trial of labor, delivered by ERCD from October 2013 to June 2014. Participants completed anonymous surveys during their delivery hospitalization. Counseling was considered adequate if women reported being counseled, recalled being quoted a VBAC success probability, and this probability was within 20% of that derived from an established VBAC success prediction model. Participants were also asked why they chose ERCD. Results Of 68 participants, only 8 (11.8%) had adequate counseling. Of those with inadequate counseling, 21.7% did not recall being counseled, 63.3% were not quoted a chance of success, and 60.0% had more than a 20% discrepancy between their recalled and predicted success rates. Eighteen women were calculated to have more than 70% chance of successful VBAC. Of these, 16 (88.9%) were not adequately counseled. Conclusion Most women were inadequately counseled about delivery options. The most important factors influencing the choice of ERCD over VBAC were patient preferences, risk for fetal injury, and perceived physician preference.